2000
DOI: 10.1097/00042560-200010010-00010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalences of HTLV-1 Infection and Associated Risk Determinants in an Urban Population in Guinea-Bissau, West Africa

Abstract: The adult population of Guinea-Bissau has a higher prevalence of HTLV-1 than reported from most other countries in West Africa. The gender-and age-specific pattern of spread of HTLV-1 closely resembles that observed for HIV-2, another retrovirus prevalent to the region. The close correlation between HTLV-1 and HIV-2 most likely reflects the shared risk factors related to sexual behavior. The implication of the high percentage of double infections in this population needs to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…In this study, HIV and HTLV-1 infections showed a cross-sectional association, as has been shown before in this study area in 1990 [25] and in the general adult population [16,41], elderly people [10], an occupational cohort [42] and pregnant women [43] in Bissau. Why this association is stronger for women than for men remains unclear.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In this study, HIV and HTLV-1 infections showed a cross-sectional association, as has been shown before in this study area in 1990 [25] and in the general adult population [16,41], elderly people [10], an occupational cohort [42] and pregnant women [43] in Bissau. Why this association is stronger for women than for men remains unclear.…”
Section: Discussionsupporting
confidence: 74%
“…Screening of blood transfusions for HIV since 1989 may have lead indirectly to a decrease of HTLV-1 in Bissau [16,41]. This mechanism seems unlikely to have played a role in the Caió area, where having received a blood transfusion was not associated with HTLV-1 infection in either 1990 [25] nor in 1997 (this risk factor was not assessed in 2007).…”
Section: Discussionmentioning
confidence: 99%
“…There are different seroprevalence rates for each continent. They range from 0% to 3.6% in Africa and from 0% to 1.5% in the Americas (with a peak of 2% in some Caribbean islands) . In Australia, the prevalence ranges from 0.001% to 0.3% and in Asia from 0% to 1.9%, while in Europe it ranges from 0% to 2.12% .…”
Section: Epidemiologymentioning
confidence: 99%
“…Other studies were performed on pregnant women or representative general adult population or on different control groups. The HTLV-1 prevalence was around 1% in Guinea, with variations from 0.2 to 1.9% depending on the region (Jeannel et al, 1995), and ranged from 2.2 to 3.6% in Guinea-Bissau (Andersson et al, 1997; Larsen et al, 2000; da Silva et al, 2009). It was of 1.2% in Gambia (Del Mistro et al, 1994) and ranged from 0.2 to 1.2% in Senegal (Hunsmann et al, 1984).…”
Section: Htlv-1 Worldwide Distribution and Prevalence Estimates By Gementioning
confidence: 99%